Academics career success: The impact of organizational context and individual variables - Emil Lucian Crisan (Rajagiri Management Journal (RAMJ), 2022)
Purpose - This study aims to address a paucity of research into career success by exploring the impact of organizational context ("in-group" culture and the competitiveness strategy) and individual variables (self-efficacy and goal orientation), on objective career success (academic position) and subjective career success (career satisfaction). Design/methodology/approach - Survey data were obtained from 447 faculty members employed by Babe÷s-Bolyai University (BBU), the best-ranked Romanian higher education institution. For analysis, hierarchical multiple regressions analyzes were used. Findings - The novel results of this quantitative analysis are that organizational context variables influence both subjective career success and objective career success. Academics who do not attain promotion have lower subjective career success and objective career success, as a result of the publish or perish university strategy. Self-efficacy has a positive impact on both success types, while goal orientation is for subjective career success a weak predictor. Practical implications - Organizational efforts should be focused on improving academics career development especially for those teachers who are in the current position already for many years. The development of performance-driven career paths should be also considered for diminishing the impact of organizational variables. Originality/value - This paper extends the knowledge concerning objective and subjective career success by revealing the important impact of contextual determinants, as it confirms the impact of individual self-efficacy in a university context and partially the one of goal orientation.
Keywords: 650; Academic position; Academics; Career satisfaction; Career success; Learning goal orientation; Self-efficacy